Effect of Blotong Compost Bio Fertilizer on Early Growth of Sugar Cane (Saccarum Officinarum) - Supandji; Edy Kustiani; Muhammad Muharram; Virgian Galuh Agusty; Yoyok Zakaria (Jurnal Online Pertanian Tropik, 2023)
Bio-compost can help increase water holding capacity, because in addition to containing a lot of organic matter, it also makes the soil hygroscopic and the structure becomes crumbly. Giving Blotong bio-compost at a dose of 80 tons / ha is very good because it increases the development of sugarcane roots and can increase production. The purpose of the study was to determine the effect of bio-compost blotong on the growth of sugarcane (Saccharum officinarum). The research was conducted in the field of Tegal which is located in the village of Blabak, Kandat sub-district, Kediri Regency. altitude of 100 masl. This research was carried out in the field using a one-factor Randomized Block Design (RAK) where the treatment factor was blotong dose: B0 = 0 tons ha-1, B1 = 5 tons ha-1, B2 = 10 tons ha-1, B3 = 15 tons ha-1, B4 = 20 tons ha-1, B5 = 25 tons ha-1. Parameters of observations made consisted of: Growth Percentage, Plant height, Number of leaves, Number of tillers, Stem diameter. The results of the research on the treatment of Blotong bio-compost fertilizer were significantly different, with the highest percentage of plant shoot growth at a dose of 20 tons ha-1, which was 89.17%. Plant height with a dose of 20 tons ha-1 is 94.75 cm. The highest number of leaves of the plant was 16.25 cm. The highest number of tillers of the sugarcane plant was 9.22 stems, the diameter of the stem of the highest sugarcane plant was 15.95 cm.